6+2=-2(8x-4)

Simple and best practice solution for 6+2=-2(8x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2=-2(8x-4) equation:



6+2=-2(8x-4)
We move all terms to the left:
6+2-(-2(8x-4))=0
We add all the numbers together, and all the variables
-(-2(8x-4))+8=0
We calculate terms in parentheses: -(-2(8x-4)), so:
-2(8x-4)
We multiply parentheses
-16x+8
Back to the equation:
-(-16x+8)
We get rid of parentheses
16x-8+8=0
We add all the numbers together, and all the variables
16x=0
x=0/16
x=0

See similar equations:

| 7-3x=-4x-13 | | x=x/9x-7 | | -4(2+4)=9-3z | | x-2(3x+6)=6-5x | | -3(x+6)-(3x-7)=-7x | | 5x+8=2x+22 | | 1/3x-6=-2/3x-8 | | -4z-6z=-2z+2-3z | | X/3x-9/x=1/2 | | 3t+16=t+412+t−212 | | j/3-10=-6 | | 2/3y+3/2=-1/12y | | 49x=180 | | 1+20=-3(6x-7) | | 34×3a=-7(1+a)+1 | | 12/3x=24 | | 4(5-p=8 | | -5(2w+11)=25 | | 2(7.5)-3c=1.5 | | 4(-3x+1)=11(x+1) | | -9x2+15x-4=0 | | 5p+2=-10p | | 5/7x+6=-2/7x+6 | | 8x^+6x=9 | | 11+x+3-13=180 | | -(x+4)=11 | | 23-15=2(x-6) | | 9a^2-27a+20=0 | | -9z-3z=7z-3-3z | | 4(z-3)-(8z-9)=-5z | | (x+3)+(3x+4)=x | | -4(n-9)=-3n-2 |

Equations solver categories